Public Listing Choice with Persistent Hidden Information - Celentano, Francesco; Rempel, Mark (Review of Economic Studies, 2026)
How much does firm intangibility amplify CEOs’ persistent private information and reduce firms’ public listing propensity? We develop a model of competing public and private investors financing firms heterogeneously exposed to persistent private cash flows. Equilibrium financing is driven by information rent differentials in CEO compensation. We validate and structurally estimate the model using firm listing and CEO compensation data. We find private (intangible) cash flows exhibit 63% higher persistence than their tangible counterparts. Further, if firm intangibility levels returned to those of 1980, mean listing propensities would increase 5 percentage points while mean CEO variable pay growth would decrease by 61%.